2007
DOI: 10.1002/jqs.1092
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and characterisation of individual glass shards from tephra deposits using trace element laser ablation ICP‐MS analyses: current status and future potential

Abstract: Pearce, Nicholas, Denton, J.S., Perkins, W.T., Westgate, J.A., (2007) 'Correlation and characterisation of individual glass shards from tephra deposits using trace element laser ablation ICP-MS analyses: current status and future potential', Journal of Quaternary Science 22(7) pp.721-736 RAE2008Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) is a high spatial resolution analytical method which has been applied to the analysis of silicic tephras. With current instrumentation, around 30 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 74 publications
0
83
1
Order By: Relevance
“…For all other major elements, the difference varies from a minimum of 0.03-1.08 (Table S2). Pearce et al (37,38) have shown that positive matching of source with distal tephra requires the difference in composition to be ≤1-2% for SiO 2 and Al 2 O 3 , and ≤5-10% for all other elements, therefore pointing to a very strong correlation between volcanic glass of the F1, F2, and F3 units of Samalas and the 1258/1259 ice-core tephra, with 1-σ error bars crossing each other for the eight major oxides.…”
Section: Discussionmentioning
confidence: 99%
“…For all other major elements, the difference varies from a minimum of 0.03-1.08 (Table S2). Pearce et al (37,38) have shown that positive matching of source with distal tephra requires the difference in composition to be ≤1-2% for SiO 2 and Al 2 O 3 , and ≤5-10% for all other elements, therefore pointing to a very strong correlation between volcanic glass of the F1, F2, and F3 units of Samalas and the 1258/1259 ice-core tephra, with 1-σ error bars crossing each other for the eight major oxides.…”
Section: Discussionmentioning
confidence: 99%
“…Where mineralogical and major-element data are unavailable, or prove insufficient or equivocal, then the next step is to obtain analyses on glass of trace and rare-earth elements (REEs) (Pearce et al, 2002(Pearce et al, , 2007Knott et al, 2007;Allan et al, 2008;Turney et al, 2008;Kuehn et al, 2009). A recent example of such a situation is that for the Sheep Creek group of tephras in western Canada and Alaska as described by Westgate et al (2008).…”
Section: Tephra Characterization and Correlation: Principlesmentioning
confidence: 99%
“…deposits (Alloway et al, 2007;Pearce et al, 2007;Lowe, 2008Lowe, , 2011. However, not every volcanic center or volcanic eruption creates globally distributed tephra layers.…”
Section: Development Of Tephra Databases and The Impact On Paleoclimamentioning
confidence: 99%
“…However, not every volcanic center or volcanic eruption creates globally distributed tephra layers. Several regional tephrochronological frameworks have been established in the last decade, e.g., for Europe (Turney et al, 2004;Newton et al, 2007;Lane et al, 2011Lane et al, , 2012 and New Zealand (Alloway et al, 2007), as well as some databases that include a wider variety of volcanic and igneous rocks. A number of regional database projects, including Tephrabase, NAVDAT, Central Andes, GeoMapApp, and GEOROC, implement data storage and availability for specific geographical regions.…”
Section: Development Of Tephra Databases and The Impact On Paleoclimamentioning
confidence: 99%
See 1 more Smart Citation